Investigating and comparing the performance of common composite columns (Journal of Civil Engineering Researchers, 2021)
In this article, I have tried to collect a set of functions of different types of composite columns. For the first time, a set ofarticles and the performance of different types of composite columns are studied, reviewed and compared. Some of theinfluential factors are: study of the behavior of various buckling modes, their performance under compressive loading withand without eccentricity, study of local and general buckling of composite columns, factors causing confinement in compositecolumns, behavior of these columns in different strength ranges from concrete alone Normal strength to high strengthconcretes, also the performance of these columns under the influence of steels with different yield stresses, the effect ofbehavioral performance of changing the thickness of steel hollow pipes, the presence or absence of steel profiles in the core ofcomposite columns and finally to verify the results The laboratory is compared with numerical methods by software toconfirm the accuracy of laboratory work as much as possible
Keywords: composite columns; steel reinforced concrete; concrete; steel; concrete filled tube